2013
DOI: 10.1002/cbin.10195
|View full text |Cite
|
Sign up to set email alerts
|

Influence of manganese on apoptosis and glutathione content of cumulus cells during in vitro maturation in bovine oocytes

Abstract: We have investigated the effect of different Mn concentrations on (1) DNA integrity of cumulus cells by olive tail moment (OTM); (2) cumulus cells apoptosis by Annexin V staining assay; (3) intracellular total glutathione (GSH-GSSG) content; and (4) oocyte nuclear maturation and embryo cleavage after in vitro fertilisation (IVF). For this purpose, 0 (control), 2 (Mn1), 5 (Mn2) and 6 ng/mL (Mn3) Mn concentrations were added to IVM medium. Comet assay analysed by OTM was significantly higher in cumulus cells ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Genotoxicity and cytotoxicity studies have been conducted to test numerous compounds using several end points on different test systems (Anchordoquy et al, 2014;Nikoloff et al, 2016;Ruiz de Arcaute et al, 2016). Numerous works have shown that the use of CC and oocyte in vitro for genotoxic and cytotoxic evaluation is a valuable and good tool for the rapid and sensitive detection of effect induced by various compound (Anguita et al, 2007;Chung et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxicity and cytotoxicity studies have been conducted to test numerous compounds using several end points on different test systems (Anchordoquy et al, 2014;Nikoloff et al, 2016;Ruiz de Arcaute et al, 2016). Numerous works have shown that the use of CC and oocyte in vitro for genotoxic and cytotoxic evaluation is a valuable and good tool for the rapid and sensitive detection of effect induced by various compound (Anguita et al, 2007;Chung et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the DNA integrity can be preserved and developmental competence of bovine oocytes to blastocyst stage can be increased through the antioxidant effect of Mn in cumulus oocyte complexes (COCs) [28]. Furthermore, the addition of Mn to maturation medium not only improved the competence of oocytes to be fertilized but also decreased the frequency of apoptotic cumulus cells [29]. Mn functions as a cofactor for several important enzymes such as arginase, pyruvate decarboxylase, and glutamine synthase [30], which are involved in DNA synthesis [31] and DNA protection [25].…”
mentioning
confidence: 99%
“…However, bovine Mn status were defined by Kincaid (1999) as deficient when Mn plasma concentration is lower than 6 ng/ml, and adequate when are between 6–70 ng/ml. Our studies have demonstrated that Mn concentrations in bovine are similar in plasma and follicular fluid (Anchordoquy et al , 2013, 2014). Adequate Mn concentration ‘protects’ cumulus cells from apoptosis (Anchordoquy et al , 2014).…”
Section: Discussionmentioning
confidence: 63%